Identifikasi Jenis Diskalkulia dari Sudut Pandang Neurosains pada Salah Satu Siswa Kelas VIIIA SMPK Santo Paulus Karuni berdasarkan Hasil Tes Siswa dan Upaya Mengatasinya - Wadu, Welhem Mine; Bulu, Sesilia Irmaya (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Many students experience difficulties in learning mathematics. One result is that students get low test scores. Students can be diagnosed with dyscalculia. Dyscalculia is difficulty in learning mathematics. The purpose of this study was to determine the type of dyscalculia from a neuroscience perspective experienced by a grade VIII student at SMPK Santo Paulus Karuni Sumba based on test results and efforts to overcome them. The type of research used is descriptive qualitative. Data collection technique is documentation. The results showed that students experienced difficulties in completing the test so that students could be said to have diagnostic and practognostic dyscalculia. Diagnostic and practognostic types of dyscalculia from the point of view of neuroscience are executive function deficits due to frontal dysfunction. The use of strategies, appropriate and fun learning methods and supported by learning media such as flash cards where the media is in accordance with the principles of neuroscience-based learning, namely orchestrated immersion, relaxed allertness and active processing can help students with this type of dyscalculia